Perioperative radiotherapy for cancer of the esophagus - Wenz, Frederik; Mamon, Harvey (Seminars in surgical oncology, 2001)
Carcinomas of the esophagus represent on average about 1% to 2% of all malignant tumors. The incidence shows extreme regional differences, reflecting the established environmental and acquired risk factors for cancer of the esophagus. There has been a major shift in tumor location and histology over the last decades, with the lower third/gastroesophageal junction becoming the most common location and adenocarcinoma the most common histology in white males. There has been a striking improvement in surgical resection rates and operative mortality; however, the curative potential of surgery is likely to be highest in early-stage disease. The poor prognosis for locally advanced tumors motivated the search for multimodal approaches to improve results. While neither perioperative radiotherapy nor perioperative chemotherapy alone have significantly improved survival rates, combined radiochemotherapy, used as neoadjuvant or definitive therapy, appears more promising. For patients with advanced tumors or extensive nodal involvement, first principles and extrapolation from other tumors of the gastrointestinal tract suggest that a combination of chemotherapy and radiation is likely to be of benefit, as compared to surgery alone. As this treatment is difficult to tolerate in the postoperative setting, neoadjuvant approaches have been emphasized. Although there are promising data, and preoperative chemoradiation is widely utilized, we do not consider the benefit of this approach to have been proven unequivocally. Future progress in the treatment of esophageal cancer may require that systemic therapy be improved to the point where occult metastatic disease can be controlled, enabling the local control provided by surgery and radiation to lead to improved survival.
Gesehen am 21.03.2022